Review of Eriosema (Leguminosae) of Florae Fluminensis from São Paulo state, Brazil - de Menezes, Helen F.; de Queiroz, Luciano P.; Remor, Danielle; Pastore, José Floriano B. (Phytotaxa, 2023)
Two taxonomic novelties in Eriosema were found during the review of Leguminosae names published in Vellozo’s Florae Fluminensis, in which Cytisus brasiliensis and C. unilateralis were revised and combined in Eriosema (respectively as E. brasiliense and E. unilateralis). The reviews included field expeditions to the most likely original localities of the species (Estrada Real de Cunha, in the state of São Paulo, Brazil), providing the analysis of herbarium specimens, taxonomic notes, morphological taxonomic plates, and distribution maps. The newly combined names were lectotypified, with epitypes collected in their most likely typical locations. A new occurrence for the Eriosema brasiliense species was recorded for the state of São Paulo.